Estimating The Knowledge of Zakat Payment Among Muslims Using The Elasticity Between Income and Zakat Expenses - Farisi, Muhammad Salman Al; Maulana, Rizky; Kumala, Destiana; Hasan, Sawqi Saad El (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2022)
This study aims to determine how the Muslims in Indonesia understanding and practicing the payment of professional zakat according to the rule. This study uses a quantitative approach with logistic regression analysis techniques to analyze whether the increase in income among the Muslims is followed by an increase in the amount of professional zakat paid by them. Therefore, logistic regression was used to analyze the two variables (income and amount of professional zakat paid) in the form of elasticity. In addition, this study also uses other supporting variables such as age, education level, type of work, job level, and religiosity so that the research model can explain the issue even better. Since the professional zakat is zakat paid by Muslims who are already working and meet the nisab, this study uses primary data of 126 Muslim respondents who were an employee and have a nisab-required salary the salary that met the nisab of professional zakat. The results of this study indicate that the income have a significant effect on the payment of professional zakat.